Heroes In Training : Perseus and the Monstrous Medusa - Joan Holub (India Simon & Schuster, 2016)
Perseus and the Olympians face off against the Monstrous Medusa in this Heroes in Training adventure.
Keywords: Myths & Legends -- Myths & Legends